Integration #7 (Corrected)

Calculus Level 3

x ( x y 2 ) = x 3 + y 2 x\left(x-y^2\right)=x^3+y^2

Find the area bounded by above curve to three decimal places.


The answer is 0.4292037.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Leonel Castillo
Jan 30, 2018

Rewrite the expression as x 2 y 2 = x 3 + x y 2 x^2 - y^2 = x^3 + xy^2 . Then do the substitution (polar coordinates) x = r cos θ , y = r sin θ x = r \cos \theta, y = r \sin \theta . This turns the expression into r 2 ( cos 2 θ sin 2 θ ) = r 3 ( cos 3 θ + cos θ sin 2 θ ) cos 2 θ sin 2 θ = r cos θ ( cos 2 θ + sin 2 θ ) r cos θ = cos 2 θ sin 2 θ r = cos θ sin θ tan θ r^2 (\cos^2 \theta - \sin^2 \theta) = r^3 ( \cos^3 \theta + \cos \theta \sin^2 \theta) \implies \cos^2 \theta - \sin^2 \theta = r \cos \theta ( \cos^2 \theta + \sin^2 \theta ) \implies r \cos \theta = \cos^2 \theta - \sin^2 \theta \implies r = \cos \theta - \sin \theta \tan \theta . Here is a graph of the shape of the function:

The closed curve is bounded by the values the function takes in two successive values of θ \theta such that r = 0 r = 0 so let's solve for that: cos θ sin θ tan θ = 0 sin θ tan θ = cos θ tan 2 θ = 1 θ = π n 2 π 4 \cos \theta - \sin \theta \tan \theta = 0 \implies \sin \theta \tan \theta = \cos \theta \implies \tan^2 \theta = 1 \implies \theta = \frac{\pi n}{2} - \frac{\pi}{4} . Plugging in n = 0 , 1 n=0,1 we get the bounds π 4 θ π 4 -\frac{\pi}{4} \leq \theta \leq \frac{\pi}{4} . With this we can describe the area via by following double integral:

π 4 π 4 0 cos θ sin θ tan θ r d r d θ = 1 2 π 4 π 4 ( cos θ sin θ tan θ ) 2 d θ = 1 2 π 4 π 4 cos 2 θ 2 cos θ sin θ tan θ + sin 2 θ tan 2 θ d θ = 1 2 π 4 π 4 cos 2 θ 2 cos θ sin θ sin θ cos θ + ( 1 c o s 2 θ ) sin 2 θ cos 2 θ d θ = 1 2 π 4 π 4 cos 2 θ 2 sin 2 θ + tan 2 θ sin 2 θ d θ = 1 2 π 4 π 4 cos 2 θ + tan 2 θ 3 sin 2 θ d θ \Large \int_{-\frac{\pi}{4}}^{\frac{\pi}{4}} \int_{0}^{ \cos \theta - \sin \theta \tan \theta} r dr d \theta = \frac{1}{2} \int_{-\frac{\pi}{4}}^{\frac{\pi}{4}} (\cos \theta - \sin \theta \tan \theta)^2 d \theta = \frac{1}{2} \int_{-\frac{\pi}{4}}^{\frac{\pi}{4}} \cos^2 \theta - 2 \cos \theta \sin \theta \tan \theta + \sin^2 \theta \tan^2 \theta d \theta \\ = \frac{1}{2} \int_{-\frac{\pi}{4}}^{\frac{\pi}{4}} \cos^2 \theta - 2 \cos \theta \sin \theta \frac{\sin \theta}{\cos \theta} + (1 - cos^2 \theta)\frac{\sin^2 \theta}{\cos^2 \theta} d \theta = \frac{1}{2} \int_{-\frac{\pi}{4}}^{\frac{\pi}{4}} \cos^2 \theta -2 \sin^2 \theta + \tan^2 \theta - \sin^2 \theta d \theta = \frac{1}{2} \int_{-\frac{\pi}{4}}^{\frac{\pi}{4}} \cos^2 \theta + \tan^2 \theta - 3 \sin^2 \theta d\theta

This is now a sum of standard trigonometric integrals and it is equal to 1 2 ( 4 π ) = 2 π 2 \frac{1}{2} ( 4 - \pi) = 2 - \frac{\pi}{2} .

Steven Yuan
Jan 30, 2018

Rewrite the equation to isolate each variable:

x ( x y 2 ) = x 3 + y 2 x 2 x y 2 = x 3 + y 2 x 2 x 3 = y 2 + x y 2 x 2 ( 1 x ) = y 2 ( 1 + x ) y 2 = x 2 ( 1 x ) 1 + x . \begin{aligned} x(x - y^2) &= x^3 + y^2 \\ x^2 - xy^2 &= x^3 + y^2 \\ x^2 - x^3 &= y^2 + xy^2 \\ x^2(1 - x) &= y^2(1 + x) \\ y^2 &= \dfrac{x^2(1 - x)}{1 + x}. \end{aligned}

If we graph this function, we see that it encloses a loop in the interval x [ 0 , 1 ] . x \in [0, 1]. Since the function is symmetric over the x-axis, we can find the area of the top portion of this loop then multiply by two. The top portion is bounded by the x-axis and the graph of

y = x 2 ( 1 x ) 1 + x = x ( 1 x ) 1 x 2 , y = \sqrt{\dfrac{x^2(1 - x)}{1 + x}} = \dfrac{x(1 - x)}{\sqrt{1 - x^2}},

so we must find 0 1 x ( 1 x ) 1 x 2 d x . \displaystyle \int_0^1 \dfrac{x(1 - x)}{\sqrt{1 - x^2}} \, dx. Make the substitution θ = arcsin x . \theta = \arcsin x. Then, we have x = sin θ x = \sin \theta and d θ = d x 1 x 2 . d \theta = \dfrac{dx}{\sqrt{1 - x^2}}. When x = 0 , x = 0, θ = 0 , \theta = 0, and when x = 1 , x = 1, θ = π 2 . \theta = \dfrac{\pi}{2}. All these substitutions yields

0 1 x ( 1 x ) 1 x 2 d x = 0 π 2 ( sin θ ) ( 1 sin θ ) d θ = 0 π 2 ( sin θ sin 2 θ ) d θ = 0 π 2 ( sin θ 1 cos 2 θ 2 ) d θ = 0 π 2 ( sin θ + 1 2 cos 2 θ 1 2 ) d θ = [ cos θ + 1 4 sin 2 θ 1 2 θ ] 0 π 2 = ( 0 + 0 π 4 ) ( 1 + 0 0 ) = 1 π 4 . \begin{aligned} \displaystyle \int_0^1 \dfrac{x(1 - x)}{\sqrt{1 - x^2}} \, dx &= \displaystyle \int_0^{\frac{\pi}{2}} (\sin \theta)(1 - \sin \theta) \, d \theta \\ &= \displaystyle \int_0^{\frac{\pi}{2}} (\sin \theta - \sin^2 \theta) \, d \theta \\ &= \displaystyle \int_0^{\frac{\pi}{2}} \left (\sin \theta - \dfrac{1 - \cos 2 \theta}{2} \right ) \, d \theta \\ &= \displaystyle \int_0^{\frac{\pi}{2}} \left (\sin \theta + \dfrac{1}{2} \cos 2 \theta - \dfrac{1}{2} \right ) \, d \theta \\ &= \left [ - \cos \theta + \dfrac{1}{4} \sin 2 \theta - \dfrac{1}{2} \theta \right ]_0^{\frac{\pi}{2}} \\ &= \left ( 0 + 0 - \dfrac{\pi}{4} \right ) - (-1 + 0 - 0) \\ &= 1 - \dfrac{\pi}{4}. \end{aligned}

The total area is twice this value, which is 2 π 2 0.429 . 2 - \dfrac{\pi}{2} \approx \boxed{0.429}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...